700 EphA2/CD137 Bicycle tumor-targeted immune cell agonists (TICAsTM) induce tumor regressions, immunogenic memory, and reprogramming of the tumor immune microenvironment. (9th November 2020) - Hurov, Kristen; lahdenranta, Johanna; Mudd, Gemma; Upadhyaya, Punit; Repash, Elizabeth; Ma, Jun; Kristensson, Julia; Kleyman, Marianna; Kublin, Jessica; Chen, Liuhong; Haines, Eric; Battula, Sailaja; et al.
Abstract : Background: Despite compelling preclinical data, agonistic anti-CD137 antibodies have been hampered by failure to delineate hepatotoxicity from efficacy in clinical studies. 1 2 A new generation of both systemic and targeted CD137 agonists that are now entering clinical development rely on biologic agents with suboptimal properties for CD137 agonism due to their relatively large sizes and long circulating half-lives. 3–5 These properties may limit their tissue penetration and cause sustained agonism resulting in overstimulation and activation-induced cell death of lymphocytes due to continuous exposure.BCY12491 is a tumor-targeted immune cell agonist (TICA TM ) that exemplifies a new class of fully synthetic immunomodulators with constrained bicyclic peptides (Bicycles®) targeting a tumor antigen and a co-stimulatory molecule. We developed this new class of synthetic molecules with antibody-like affinities and target selectivity to circumvent the beforementioned barriers to optimal targeted CD137 agonistic therapeutics. BCY12491 (EphA2/CD137 TICA) is designed to deliver a highly potent CD137 agonist to EphA2 overexpressing tumor tissue with an intermittent dosing schedule maximizing anti-tumor activity while circumventing the need for continuous systemic exposure. Methods: BCY12491 bioactivity was assessed in vitro using a CD137 reporter assay and by measuring cytokine production from primary human PBMC/tumor cell co-cultures. BCY12491 in vivo activity was determined in huCD137-syngeneic tumor models by measuring tumor growth kinetics and using tumor immune cell and transcriptional profiling by FACS, IHC, and Nanostring. Results: BCY12491 engages EphA2 and CD137 with high affinity resulting in picomolar potency in co-culture assays consisting of EphA2-expressing tumor cell lines and CD137-expressing Jurkat NF-kappaB-luciferase reporter cells. Moreover, BCY12491 caused EphA2-dependent CD137 agonism in primary human PBMCs co-cultured with tumor cells with varied levels of EphA2 expression. Treatment of MC38 tumors in immunocompetent mice with BCY12491 leads to a profound reprogramming of the tumor immune microenvironment including increased T cell infiltration and stimulation of NF-kappaB signaling, costimulatory signaling, cytotoxicity and cytokine/chemokine signaling functional pathways. BCY12491 treatment leads to MC38 tumor regressions, complete responses, and immunogenic memory without continuous drug exposure in the periphery. This anti-tumor activity is dependent on CD8+ T cells, but not on NK 1.1+ cells. Conclusions: BCY12491 is a potent EphA2-dependent CD137 agonist with optimal target binding, pharmacologic, and pharmacokinetic properties that enable anti-tumor TME remodeling and complete responses in vivo with intermittent dosing. This work unleashes a new and tractable avenue to testing a novel class of therapeutic CD137 agonists in humans for the treatment of cancer. Ethics Approval: The care and use of animals were reviewed and approved by the Institutional Animal Care and Use Committee (IACUC) of WuXi AppTec and conducted in accordance with the regulations of the Association for Assessment and Accreditation of Laboratory Animal Care (AAALAC). References: Segal NH, Logan TF, Hodi FS, et al. Results from an integrated safety analysis of urelumab, an agonist anti-CD137 monoclonal antibody. Clin Cancer Res 2017;23(8):1929–1936. Chester C, Sanmamed MF, Wang J, Melero I. Immunotherapy targeting 4-1BB: mechanistic rationale, clinical results, and future strategies. Blood 2018;131(1): 49–57. Hinner MJ, Aiba RSB, Jaquin TJ, et al. Tumor-Localized Costimulatory T-Cell Engagement by the 4-1BB/HER2 Bispecific Antibody-Anticalin Fusion PRS-343. Clin Cancer Res . 2019;25(19):5878–5889. Claus C, Ferrara, C, Xu W, et al. Tumor-targeted 4-1BB agonists for combination with T cell bispecific antibodies as off-the-shelf therapy. Sci Transl Med 2019;11(496): eaav5989. Eskiocak U, Guzman W, Wolf B, et al. Differentiated agonistic antibody targeting CD137 eradicates large tumors without hepatotoxicity. JCI Insight 2020;5(5):e133647.